Antipsychotics are related to psychometric conversion to psychosis in ultra‐high‐risk youth. Issue 4 (5th May 2021) - Preti, Antonio; Raballo, Andrea; Meneghelli, Anna; Cocchi, Angelo; Meliante, Maria; Barbera, Simona; Malvini, Lara; Monzani, Emiliano; Percudani, Mauro
Abstract: Background: The prescription of antipsychotics outside overt psychotic conditions remains controversial, especially in youth where it is relatively widespread. Furthermore, some studies seem to indicate that antipsychotic exposure in individuals at ultra‐high‐risk (UHR) for psychosis is associated with higher conversion rates. This study was set up to test whether the inter‐current prescription of antipsychotics in UHR patients was related to the psychometric threshold for a diagnosis of psychosis. Methods: The 24‐item Brief Psychiatric Rating Scale (BPRS) was used to quantify treatment response up to 2 years in 125 UHR participants. Standard psychometric criteria were used to quantify conversion to psychosis. Kaplan‐Mayer and Cox proportional hazard survival analysis were applied to determine the impact of having or not received the prescription of an antipsychotic drug. Results: Over the study period 30 (24%) subjects received the prescription of an antipsychotic. In the sample, there were 31 participants (25%) who had reached the psychometric threshold for conversion to psychosis after 2 years of treatment. UHR people who received a prescription of antipsychotics during the first 2 years of treatment were statistically more likely to reach the psychometric threshold for conversion to psychosis on the BPRS: Hazard ratio = 3.03 (95%CI: 1.49–6.16); p = .003. Conclusion: This finding supports the hypothesis that the prescription of antipsychotics within UHR cohorts is to be considered a red flag for higher incipient risk of conversion to psychosis.